A global study to identify a potential basis for policy options when integrating animal welfare into the UN Sustainable Development Goals - Keeling, Linda J.; Marier, Elizabeth A.; Olmos Antillón, Gabriela; Blokhuis, Harry J.; Staaf Larsson, Birgitta; Stuardo, Leopoldo (Frontiers in Animal Science, 2022)
A previously developed methodology to rate the strength of the impact of improving animal welfare on achieving each of the 17 SDGs and the impact of achieving each SDG on animal welfare was used at the third Animal Welfare Global Forum of the World Organisation for Animal Health. Data from 95 participants from key stakeholder categories and organisations involved in animal welfare were analysed. The resulting ‘map’ of the relative strengths of these associations confirmed the expected co-benefits of improving animal welfare and achieving the SDGs. Differences at regional level and according to the economic classification of the country were also identified. This paper focuses on using this ‘map’ as a potential guide for how organisations interested in improving animal welfare could identify potential new allies for strategic partnerships to facilitate the implementation of different policy options. For example, a strategy can be to collaborate with those organisations where the impact is of similar mutual benefit, e.g. between improving animal welfare and achieving SDG 3 (Good health and well-being). Organisations in these two areas are already aligning themselves in the ‘One health’ movement. Another strategy can be to align with organisations for whom achievement of their goal has the greatest impact on animal welfare, even if the impact is not mutual e.g. by collaborating with organisations working to achieve SDG 16 (Peace justice and strong institutions) and SDG 4 (Quality education). Achieving these goals was considered to have a large impact on improving animal welfare, equivalent to that of achieving SDG 3. In summary, this study can help organisations working in the area of animal welfare identify previously untapped areas of potential support, so tailoring their efforts efficiently, while at the same time themselves supporting movement towards the Agenda 2030. Simply put, the co-benefits make collaboration worthwhile, potentially opening up opportunities that would be unavailable when organisations are working independently towards their own respective goals.